Two case reports: clinical experience with fixed combinations of indapamide/perindopril and amlodipine/perindopril in patients with arterial hypertension during the COVID-19 pandemic - S. Ia. Tazina; I. A. Belyaev; T. A. Fedorova; N. A. Semenenko; S. A. Tazin (Евразийский Кардиологический Журнал)
The article, using the example of two clinical cases, discusses the severity of the course of COVID-19 depending on the presence of cardiovascular diseases and the effectiveness of their treatment. Randomized clinical trials and meta-analyses of the coronavirus infection indicate a greater likelihood of developing severe forms of COVID-19 in patients with high and very high cardiovascular risk, in older age groups, with comorbid pathology, especially with arterial hypertension (AH), coronary heart disease (CHD), chronic heart failure (CHF), diabetes mellitus (DM). Considering effectiveness, safety and influence on the prognosis, an adequately selected therapy for concomitant diseases can reduce the number of adverse outcomes of the coronavirus infection. A key role in the development and progression of cardiovascular pathology is played by the renin-angiotensin-aldosterone system (RAAS), so RAAS blockers remain the first-line medicine in the treatment of cardiac patients. The experts of the European Society of Cardiology, the American College of Cardiology and the Russian Society of Cardiology confirm the importance of continuing therapy with this class of medicine in patients having already received RAAS blockers according to such indications as AH, CHD and CHF during COVID-19 and emphasize the danger of their cancellation in high-risk patients. Most patients need to take several groups of medicine which affect complementary pathogenetic mechanisms. It is shown that the reason for the lack of achieving blood pressure control in clinical practice is monotherapy or non-optimally combined therapy of free acceptable but not rational combinations of antihypertensive medicine. Optimization of the therapeutic regimen using fixed combinations of indapamide/perindopril and amlodipine/perindopril has made it possible to achieve an effective reduction in blood pressure according to routine measurement and ambulatory blood pressure monitoring, to reduce blood pressure variability, to increase patients’ adherence to the treatment. The use of such medicine is becoming the most relevant during the COVID-19 pandemic.